2015
DOI: 10.1515/cclm-2014-1118
|View full text |Cite
|
Sign up to set email alerts
|

Analytical evaluation of Diazyme procalcitonin (PCT) latex-enhanced immunoturbidimetric assay on Beckman Coulter AU5800

Abstract: Diazyme PCT appears to be a reliable assay for diagnosis and management of critical care patients susceptible to severe bacterial infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
13
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 9 publications
3
13
3
Order By: Relevance
“…It can be observed that for PCT-BR and PCT-BK, the between-day component of imprecision was negligible, whereas for the PCT-D, especially at lower concentrations, the between-day component was relevant. The observed LoD and the functional sensitivity for PCT-D were much higher than those declared by Diazyme (0.051 and 0.15 μg/L) [19], but in line with those published by Dipalo et al [20], whereas for PCT-BR and PCT-BK, the values were slightly better than those declared [17,18]. The reproducibility performances of PCT-BR at very low PCT concentrations are clearly superior to those of the other two systems (Figure 1).…”
Section: Performance Assessmentsupporting
confidence: 91%
See 3 more Smart Citations
“…It can be observed that for PCT-BR and PCT-BK, the between-day component of imprecision was negligible, whereas for the PCT-D, especially at lower concentrations, the between-day component was relevant. The observed LoD and the functional sensitivity for PCT-D were much higher than those declared by Diazyme (0.051 and 0.15 μg/L) [19], but in line with those published by Dipalo et al [20], whereas for PCT-BR and PCT-BK, the values were slightly better than those declared [17,18]. The reproducibility performances of PCT-BR at very low PCT concentrations are clearly superior to those of the other two systems (Figure 1).…”
Section: Performance Assessmentsupporting
confidence: 91%
“…The reproducibility performances of PCT-BR at very low PCT concentrations are clearly superior to those of the other two systems (Figure 1). The results of the linearity experiment for PCT-D were not in line with the manufacturer's specifications neither with what obtained by Dipalo et al [20]. Linearity was checked in two different experiments (same reagent lot) (see Supplemental Figure 1); moreover, the automatic dilution system of Roche for clinical chemistry assays (use of a reduced sample volume) was not successful (data not shown), so only manual dilutions with a negative serum were effective for samples with PCT concentration >25 μg/L.…”
Section: Performance Assessmentcontrasting
confidence: 84%
See 2 more Smart Citations
“…In regard to emerging technologies for PCT measurements, a study from Italy [10] evaluated the analytical performance of the novel diazyme PCT immunoturbidimetric assay on Beckman CoulterAU5800 as compared with the reference Kryptor technology. This novel technology has some technical and analytical advantages over Kryptor technology, including a lower volume of sample needed for measurements (i.e., 20 vs. 50 μL), a faster turnaround time (10 vs. 19 min), lower costs, as well as the high throughput.…”
mentioning
confidence: 99%